PENGARUH CITRA TOKO TERHADAP KEPUASAN PELANGGAN BERBELANJA PADA DISTRO BATTLEBOOM STORE DI KOTA PALU - Kamaliono, Masjaya (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study is to find out the influence of store image, consisting of store location, product, price, service, promotion, and physical facilities, on customers? shopping satisfaction at The Battleboom Store in Palu City. Type of research is quantitative. Sample consists of 100 respondents who shopped at The Battleboom Store in Palu City, who selected with a non-probability sampling technique, named purposive sampling. Method of analysis is multiple linear regressions. The result shows that store image simultaneously affects customer satisfaction. However, there are two dimensions of store image that are store location and physical facilities that have non-significant influence on customers? shopping satisfaction at The Battleboom Store in Palu City.